(untitled) - Inmon, William H. (Homewood, 1986)
The computer industry has evolved so rapidly that there has been little time to quantify the major economic trends. Using well-researched data. Technomics offers clear and objective information on the economics of the data processing industry.
Keywords: Công nghiệp máy tính,Computer industry; Hoa Kỳ,United States